The Cultural Content in EFL Textbooks and What Teachers Need to Do About It - Luis Fernando Gómez Rodríguez (Universidad Nacional de Colombia, 2015)
This article analyzes the cultural content in three communicative English as a foreign language textbooks that are used as main instructional resources in the English classroom. The study examined whether the textbooks include elements of surface or deep culture, and the findings indicate that the textbooks contain only static and congratulatory topics of surface culture and omit complex and transformative forms of culture. Consequently, the second part of the article suggests how teachers can address deep-rooted aspects of culture that might help English as a foreign language learners build more substantive intercultural competence in the language classroom.